Legal knowledge engineering : a modelling approach - Valente, A. (IOS Press, 1995)
Current approaches to the development of legal knowledge-based systems (LKBS), such as the use of rule-based systems, case-based systems or logics, have obtained limited theoretical and practical results. This overview of the field describes present approaches and analyzes their problems